Reparo periapical de dentes tratados endodonticamente submetidos a movimentação ortodôntica - Ribeiro, Alexandre Antonio [UNESP]|Caldas, Sergei Godeiro Fernandes Rabelo [UNESP]; Martins, Lídia Parsekian [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Tanomaru Filho, Mário [UNESP] (My University, 2012)
The relationship of Orthodontics and Endodontics is being clarified with the development of evidence-based dentistry. However, few studies have reported the repair of periapical lesions with orthodontic treatment. Therefore, the aim of this study was to evaluate the available evidence on periapical repair of endodontically treated teeth during orthodontic movement. The strategy used was the electronic search with keywords and criteria including studies published up to July 2011. It was also carried out qualitative assessment of the articles methodology. Although a significant number of studies have reported this topic, only two filled the criteria for inclusion in this systematic review. The results obtained in the literature suggest that orthodontic treatment should be interrupted to perform endodontic treatment. During this therapy, the use of root canal dressing based on calcium hydroxide for at least 14 days, and sealer with adequate biological property are indicated. After this phase, orthodontic movement of the endodontically treated teeth can be resumed without waiting period.

A inter-relação Ortodontia e Endodontia vem sendo esclarecida com a evolução da Odontologia baseada em evidências científicas. Contudo, poucos estudos relacionam o reparo periapical de lesões com movimentação ortodôntica. Sendo assim, o objetivo deste estudo foi avaliar a evidência científica disponível sobre o reparo periapical de dentes tratados endodonticamente durante a movimentação ortodôntica. A estratégia usada foi a de busca eletrônica com palavras-chaves e critérios incluindo artigos publicados até julho de 2011. Foi também realizada avaliação qualitativa da metodologia dos artigos. Embora um significativo número de estudos reportarem o assunto, apenas dois artigos preencheram os critérios para inclusão nesta revisão sistemática. Os resultados obtidos na literatura sugerem que o tratamento ortodôntico deve ser interrompido para realização do tratamento endodôntico. Durante esta terapia, o emprego de curativo de demora à base de hidróxido de cálcio por no mínimo 14 dias e de cimento endodôntico com adequada propriedade biológica estão indicados. Após esta fase, a movimentação ortodôntica do dente tratado endodonticamente pode ser retomada sem necessidade de período de espera.
Periapical repair of endodontically treated teeth submitted to orthodontic movement: a systematic review
Keywords: Endodontics; Periapical tissue; Orthodontics; Tooth movement; Endodontia; Tecido periapical; Ortodontia; Movimento dentário